Mineral Trioxide Aggregate v/s Calcium Hydroxide: A Review Article - Gayatri Padhee1 Susant Mohanty (Institute of Medico-legal Publications Pvt Ltd, 2020)
The main purpose of this article is to compare the mineral trioxide aggregate and calcium hydroxide inpediatric dentistry. Both of the endodontic cement are frequently used in different cases of pedodontics. Thisarticle aims to present the various characteristics of mineral trioxide aggregate and calcium hydroxide in areview article.